(untitled) (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
Language, as a uniquely human capacity, serves not only as a tool for communication but also as a reflection of cognitive processes and social structures. Linguistics, the scientific study of language, explores its sound systems, structures, meanings, and variations across societies and time. This article delves into the core branches of linguistics, including phonetics, morphology, syntax, semantics, sociolinguistics, and psycholinguistics, highlighting their contributions to understanding language. Additionally, it examines key debates such as universal grammar and addresses the real-world applications of linguistic science in education, technology, and cultural preservation. Linguistics emerges as both a scientific and humanistic field, central to exploring human nature.